Distance Learning In An Educational Perspective In Indonesia During The Covid-19 Pandemic - Budi Ilham Maliki; Jaka Wijaya Kusuma; Mulyadi Mulyadi; Ranny Meilisa; Hamidah Hamidah (Jurnal Educatio FKIP UNMA, 2021)
The Existence of the Covid-19 pandemic has a serious impact on teaching and learning activities at various levels and types of educational institutions that were originally face-to-face in the classroom shifted into distance education (distance learning) in the network (online) with online systems (direct) and offline (delay). This study aims to find out how distance learning in the perspective of education in Indonesia during the current Covid-19 pandemic? What's the concept? What are the problems and challenges? And what's the solution? To answer the question above, the method used is the study of the library, namely in this case the author tries to study some available literature to get an explanation relevant to the problem so that the problems in this paper can easily be answered.The results of the literature study stated that (1) Distance learning in an educational perspective in Indonesia, is the implementation of education whose learners are separated from educators and their learning by using various learning resources through information and communication technology, and other media, which serves as a form of education for learners who cannot attend face-to-face education and aims to increase the expansion and equitable access to quality and relevant education as needed; (2) Distance learning during the Covid-19 Pandemic through online learning is focused on life skills education by online or online distance learning methods and offline or offline distance learning.In conclusion, during the Covis-19 pandemic, our education system must be ready to make the leap to transform online learning for all students and by all teachers to enter a new era of building creativity, honing students' skills, and improving self-quality with system changes, perspectives and patterns of our interaction with technology.